Effects of HR policies on organizational performance in the Korean public sector: moderation roles of the JD-R model - Lee, Yoonjin; Kim, Min Young (Frontiers in Organizational Psychology, 2025)
This study investigates the impact of Family-Friendly Policies (FFPs) and Employee Welfare Policies (EWPs) on employee wellbeing and organizational outcomes in the Korean public sector, with a particular focus on the moderating role of job demands and resources. Utilizing data from the 2023 Public Employee Perception Survey (n = 6,444), the study adopts the Job Demands–Resources (JD-R) framework to examine how satisfaction with HR policies influences employees' quality of life (QOL), public service satisfaction, and turnover intention. Hierarchical multiple regression analyses revealed that satisfaction with both FFPs and EWPs positively influenced QOL and public service satisfaction. However, EWP satisfaction showed a more robust and consistent association across all outcomes, including a significant negative relationship with turnover intention. Among the JD-R variables, job stress and autonomy emerged as significant predictors of employee outcomes. Importantly, interaction effects were observed: the turnover-reducing effect of FFP satisfaction was amplified under conditions of high job autonomy, whereas the influence of EWP satisfaction slightly weakened in similar contexts. These findings contribute to the theoretical integration of HRM and the JD-R model, highlighting the interplay between policy-level support and workplace conditions. Practically, the study offers actionable insights for public sector managers aiming to enhance workforce sustainability through integrated and context-sensitive HR strategies—particularly relevant for governments navigating evolving employee expectations and complex administrative challenges.